Design and Optimization of Simvastatin Self-Microemulsifying Drug Delivery System for Enhanced Therapeutic Potential (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: In present study, a self-microemulsifying drug delivery system (SMEDDS) has been developed and optimized to enhance solubility and bioavailability of poorly water soluble drug simvastatin. Material and Methods: Phase solubility studies and emulsification tests were performed for selection of a suitable oil, surfactant, and co- solvent. A three factor, two level, mixture design of experiments was used to optimize the concentration of components for SMEDDS formulation for achieving excellent physicochemical properties such as small globule size (